The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1007/s00384-018-3111-x
|View full text |Cite
|
Sign up to set email alerts
|

Robotic-assisted total mesorectal excision (TME) for rectal cancer results in a significantly higher quality of TME specimen compared to the laparoscopic approach—report of a single-center experience

Abstract: Robotic surgery is safe and can improve the quality of TME for rectal cancer compared to laparoscopy. Any effect on long-term survival remains to be established.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 24 publications
0
34
1
Order By: Relevance
“…The pooled data showed no significant difference was observed between robotic group (1.89%, 18/950) and laparoscopic group (1.77%, 17/960) (OR = 1.12, 95% CI 0.58-2.17, P = 0.74), with no significant heterogeneity among the studies (I 2 = 0%, P = 0.79). Of the 8 studies, 3 studies [19,25,26] clearly reported the site of bleeding in the anastomotic stoma, with an incidence of 3.30% (7/212) in RS group and 5.63% (9/160) in LS group. The meta-analysis showed no significant difference (OR = 0.64, 95% CI 0.23-1.77, P = 0.39) and no heterogeneity (I 2 = 0%, P = 0.81).…”
Section: Plos Onementioning
confidence: 99%
“…The pooled data showed no significant difference was observed between robotic group (1.89%, 18/950) and laparoscopic group (1.77%, 17/960) (OR = 1.12, 95% CI 0.58-2.17, P = 0.74), with no significant heterogeneity among the studies (I 2 = 0%, P = 0.79). Of the 8 studies, 3 studies [19,25,26] clearly reported the site of bleeding in the anastomotic stoma, with an incidence of 3.30% (7/212) in RS group and 5.63% (9/160) in LS group. The meta-analysis showed no significant difference (OR = 0.64, 95% CI 0.23-1.77, P = 0.39) and no heterogeneity (I 2 = 0%, P = 0.81).…”
Section: Plos Onementioning
confidence: 99%
“…After removing duplicates, 739 publications were further reviewed. Further screening found that 23 studies [15][16][17][18][19][20][21][22][24][25][26][27][28][29][30][31][32][33][34][35][36]47,48 met the predefined inclusion criteria. The selection process is reported in Figure 2.…”
Section: Literature Search and Study Characteristicsmentioning
confidence: 99%
“…The selection process is reported in Figure 2. Among the included studies, eight were prospective, 24,25,28,29,32,34,35,48 and 15 retrospective. [15][16][17][18][19][20][21][22]26,27,30,31,33,36,47 F I G U R E 1 Network geometry for studies reporting A, complete mesorectum excision; B, near complete mesorectum excision; C, incomplete mesorectum; D, radial margin involvement; E, lymph node harvest; F, local recurrence; G, distal recurrence; H, overall complication rate; I, anastomotic leak; L, wound infection; M, urinary dysfunction; N, bowel obstruction; O, reoperation; and P, 30-day mortality.…”
Section: Literature Search and Study Characteristicsmentioning
confidence: 99%
“…In the current study, 19 patients (90.6%) were classi ed as the grading of "complete" in the R-TME group. Similarly, in the literature, Kim et al [28] reported 32 "complete" patients (97.0%) and Aselmann et al [29] reported 43 "complete" patients (97.7%). However, the high-quality evidence from the ROLLAR trail showed that 178 patients (75.4%) were classi ed as "complete" [19], signi cantly lower than our result.…”
Section: Discussionmentioning
confidence: 72%